Assessment of multi-professional primary healthcare center quality by patients with multimorbidity - Antoine Dany; Paul Aujoulat; Floriane Colin; Jean-Yves Le Reste; Delphine Le Goff (BMC, 2024)
Abstract Background The main aim of this study was to build an item bank for assessing the care quality of multi-professional healthcare centers (MPHCC) from the perspective of patients with multimorbidity. This study was part of the QUALSOPRIM (QUALité des SOins PRIMaires; primary healthcare quality) research project to create a psychometrically robust self-administered questionnaire to assess healthcare quality. Methods First, twelve experts built an item bank using data from a previous qualitative work and a systematic literature review. Second, the validity of each item was assessed in a sample of patients. Adult patients with multimorbidity were recruited from six French MPHCC. Items were assessed based on ceiling effects, the level of missing or neutral responses and patient feedback. Patient feedback was recorded after the item bank completion. Based on results, items were validated, improved, or removed during expert meetings. In case of disagreement the Delphi method was used to reach consensus. Results The study sample included 209 outpatients. The most frequent medical conditions were cardiovascular risk factors, cardiovascular diseases and rheumatological conditions. In total, a bank of 109 items classified in nine domains was built. The validity assessment led to the removal of 34 items. Retained items explored a variety of topics related to care quality: availability, accessibility, premises' layout and building, technical care, expertise, organization, relationships with caregivers and communication, involvement and personal relationships. Conclusions This study allowed cross-validation of a bank of 75 items, leading to a complete picture of the patient perception of care quality items. Overall, patients were generally satisfied with their care at the MPHCC. Nonetheless, there were still numerous items on subjects for which patients' satisfaction could be improved.